Large-Scale Computational Discovery of Binding Motifs in tRNA Fragments - Guan, Lingyu; Lam, Vincent; Grigoriev, Andrey (Frontiers in Molecular Biosciences, 2021)
Accumulating evidence has suggested that tRNA-derived fragments (tRFs) could be loaded to Argonaute proteins and function as regulatory small RNAs. However, their mode of actions remains largely unknown and investigations of their binding mechanisms have been limited, revealing little more than microRNA-like seed regions in a handful of tRFs and a few targets. Here, we identified such regions of potential interaction on a larger scale, using in vivo formed hybrids of guides and targets in crosslinked chimeric reads in two orientations. We considered “forward pairs” (with guides located on the 5’ ends and targets – on the 3’ ends of hybrids) and “reverse pairs” (opposite orientation) and compared them as independent sets of biological constructs. We observed intriguing differences between the two chimera orientations, including the paucity of tRNA halves and abundance of polyT-containing targets in forward pairs. We found a total of 197 quality-ranked motifs supported by 120,000 tRF-mRNA chimeras, with 103 interacting motifs common in forward and reverse pairs. By analyzing T→C conversions in human and mouse PAR-CLIP datasets, we detected Argonaute crosslinking sites in tRFs, conserved across species. We proposed a novel model connecting the formation of asymmetric pairs in two sets to the potential binding mechanisms of tRFs, involving the identified interaction motifs and crosslinking sites to Argonaute proteins. Our results suggest the way for further experimental elucidation of tRF binding mechanisms.